Cyclical modulation of human ventricular repolarization by respiration - Hanson, Ben; Gill, Jaswinder; Western, David; Gilbey, Michael; Bostock, Julian; Boyett, Mark R.; Zhang, Henggui; Coronel, Ruben; Taggart, Peter (Frontiers in Physiology, 2012)
Background: Respiratory modulation of autonomic input to the sinus node results in cyclical modulation of heart rate, known as respiratory sinus arrhythmia. We hypothesized that the respiratory cycle may also exert cyclical modulation on ventricular repolarization, which may be separately measurable using local endocardial recordings. Methods and Results: The study included 16 subjects with normal ventricles undergoing routine clinical electrophysiological procedures for supraventricular arrhythmias. Unipolar electrograms were recorded from 10 right and 10 left ventricular endocardial sites. Breathing was voluntarily regulated at 5 fixed frequencies (6, 9, 12, 15 and 30 breaths per minute) and heart rate was clamped by RV pacing. Activation-recovery intervals (ARI: a surrogate for APD) exhibited significant (p<0.025) cyclical variation at the respiratory frequency in all subjects; ARI shortened with inspiration and lengthened with expiration. Peak-to-peak ARI variation ranged from 0-26 ms; the spatial pattern varied with subject. Arterial blood pressure also oscillated at the respiratory frequency (p<0.025) and lagged behind respiration by between 1.5 s and 0.65s from slowest to fastest breathing rates respectively. Systolic oscillation amplitude was significantly greater than diastolic (14±5 vs. 8±4 mmHg ± SD, p<0.001). Conclusions: Observations in humans with healthy ventricles using multiple left and right ventricular endocardial recordings showed that ARI (APD) varied cyclically with respiration.